Specular vision-touch synaesthesia: two reference frames. - White, R; Davies, A (2012)
Two subtypes of vision-touch synaesthesia (VTS) have been identified. For anatomical VTS, sight of touch on another person elicits synaesthetic tactile sensation at the same location on the observer's own body (e.g., viewed touch on the left cheek elicits sensation on the observer's left cheek). For specular VTS, sight of touch on another person elicits synaesthetic tactile sensation at the mirror-reflected location (e.g., viewed touch on the left cheek elicits sensation on the observer's right cheek). Here we report two distinctly different patterns of sensation within the specular subtype. Both participants experienced synaesthetic tactile sensation on their right hand when they viewed unidirectional brushstrokes administered to a prosthetic left hand (positioned with fingers pointing toward the participant), but the direction of sensation matched the viewed touch in a hand-centred (spatial) reference frame for RS and in an external (viewer-centred) reference frame for NC. Competing reference frames affect how individuals with specular VTS experience synaesthetic tactile sensation.